Periodontitis, association with ischemic cardiovascular disease - López-Ilisástigui, Alina (2021)
Objective. Determine the association between periodontitis and ischemic heart disease. Methods. Cross-sectional, analytical case-control study. From the universe of 9,350 individuals between the ages of 35 and 70 years of both sexes, residents in the Plaza de la Revolution municipality, who had at least six teeth in the mouth and in their medical history the results of complementary tests to detect dyslipidemia In the last six months, a sample of 1,200 individuals who gave their consent to participate was selected by the simple random method. The case group consisted of 600 subjects with a medical diagnosis of ischemic cardiovascular disease during the five years prior to the investigation and the control group for the same number of subjects, without this antecedent. The groups were matched in relation to age and sex. The variables studied were: history of ischemic cardiovascular disease in the last five years, presence and severity of periodontitis, teeth lost due to periodontitis and loss of periodontal attachment. The association between the presence of periodontitis and ischemic cardiovascular disease, the odds ratio (OR) was used, with its corresponding 95% confidence intervals. In addition, the Chi square of independence was applied with a significance level of 0.05. Results. A high intensity of association with periodontitis is observed (OR = 4.07). in the cases, not so in the controls. The cases also presented greater severity, missing teeth and loss of attachment than the controls. Conclusions. A strong association between periodontitis and ischemic cardiovascular disease was detected in this study.